KNOWLEDGE MANAGEMENT MATURITY ASSESSMENT ON A PETROCHEMICAL COMPANY - Agita Devani, Vannya
Sustainable petrochemical company growth has brought multiplier effect to Indonesia’s economic activities. Petrochemical industry has supported the country’s production needs in a numerous downstream manufacturing by providing raw material for numerous products, such as plastics production, textile as well as automotive parts production. PT Citra Biru Perkasa (CBP) is the largest publicly listed petrochemical company in Indonesia. CBP is the only petrochemical company that has Naphtha Cracker producing high quality of Olefins and Polyolefin. In addition, CBP is the only company that produces Styrene Monomer and Butadiene. Importance and relevance of knowledge in today’s business era has become more and more critical as it transitioned into information and knowledge era. CBP is aware that Human Resource (HR) has an important role in realizing company’s strategic objectives. Every employee in the company hold critical knowledge in a form of tacit knowledge. Knowledge is a critical resource that provide sustainable competitive advantage and considered as the company asset. Companies that has apply knowledge management is proven to increase company competitiveness. Company’s knowledge is continually shaped by employee’s new experiences. Knowledge management help to achieve company strategic objective and have competitive advantages through the best use of knowledge. Considering the number of petrochemical company in the country increasing and seeing how the trend is now shifting into information and knowledge era, CBP plan to establish good knowledge management (KM) in the company. In order to do that, first CBP has to know the company’s current KM maturity. CBP KM maturity assessment is done based on Asian Productivity Organization (APO) Framework. Assessing knowledge management maturity level of the company could help CBP in the analysis of knowledge gap and development of knowledge management can be carried out in the form of implementation plan. This research was conducted in order to answer three research question. First, how is the current knowledge management maturity level in both CBP manufacturing and non-manufacturing. Second, what are the knowledge gaps to be identified and to be filled to support business objective of the company. Third, how should knowledge management implementation plans be developing to support the company’s business objectives. This research uses qualitative and quantitative data collection. Quantitative data collection is done through online survey done to measure CBP knowledge management maturity level. The online survey is compiled based on APO Framework seven categories list of indicators, which are leadership, people, process, technology, knowledge process, learning and innovation, and KM outcomes. The answer then processes and formulated into a fishbone analysis to identify key success factor for CBP knowledge management. Qualitative data collection is done through interview to get more empirical information on the current KM practice in CBP. The interview questions developed try to capture the readiness in implementing and incorporating KM in the company. The result shows that there are several knowledge gap in the company that needed improvement. CBP non-manufacturing KM maturity level is in the refinement level meaning that CBP non-manufacturing has already have KM that is continually evaluated for continuous improvement. Meanwhile, CBP KM maturity level is in expansion level meaning that KM is already implemented and deployed. Even though the different level on both CBP non-manufacturing and manufacturing the business solution proposed is to be implemented in both.